The Impact of Social Media on Individuals’ Participation in Political Events (The International Journal of Educational Sciences and Arts, 2023)
Since the beginning of 2011, Egypt, like many other Arab countries, has witnessed a wave of protests, sit-ins, and marches demanding reform changes in the political, economic, and social fields. Social media has allowed the organizers of the events of this mass movement to participate and interact with the events, at the level of motivation and mobilization of general opinion. This study aimed to identify the role of social media in motivating citizens to participate in mass movement activities, using the media survey method, both descriptive and analytical, on a sample of (296) individuals from trade unionists in the city of Zagazig. One of the most prominent findings of this study was that (56.6%) of trade unionists participate (always, sometimes, and rarely) in the mass movement demanding reform and change in Egypt, through social media. The results showed that there is no statistically significant relationship between the demographic characteristics of trade unionists and participation in the mass movement via social media.
Keywords: Social media; political events; sociology